Health-Economic Value of Vaccination Against Group A Streptococcus in the United States. (30th June 2021) - Andrejko, Kristin; Whittles, Lilith K; Lewnard, Joseph A
Abstract: Background: Vaccines are needed to reduce the burden of group A Streptococcus (GAS). We assessed the potential health-economic value of GAS vaccines achievable through prevention of invasive disease and acute upper respiratory infections in the United States. Methods: We estimated annual incidence of invasive GAS disease and associated costs incurred from hospitalization and management of long-term sequelae, as well as productivity losses resulting from acute illness, long-term disability, and mortality. We also estimated healthcare and productivity costs associated with GAS pharyngitis, sinusitis, and acute otitis media. We estimated costs averted by prevention of invasive disease and acute upper respiratory infections for vaccines with differing efficacy profiles; our base case considered vaccines meeting the World Health Organization Preferred Product Profile (WHO-PPP) with a 6-year average duration of protection. Results: Costs of invasive GAS disease and acute upper respiratory infections totaled $6.08 (95% confidence interval [CI], $5.33–$6.86) billion annually. Direct effects of vaccines meeting WHO-PPP characteristics and administered at ages 12 and 18 months would avert $609 (95% CI, $558–$663) million in costs annually, primarily by preventing noninvasive disease; with an additional dose at age 5 years, averted costs would total $869 (95% CI, $798–$945) million annually. Adult vaccination at age 65 years would avert $326 (95% CI, $271–$387) million in annual costs associated with invasive GAS disease. Indirect effects of vaccination programs reducing incidence of GAS diseases across all ages by 20% would avert roughly $1 billion in costs each year. Conclusions: The economic burden of GAS is substantial. Our findings should inform prioritization of GAS vaccine development and evaluation. Abstract : Group A Streptococcus causes roughly $5.3–$6.9 billion in healthcare and productivity costs annually in the United States due to acute upper respiratory infections and invasive disease. Prevention of pharyngitis is central to the economic value of pediatric vaccination.